2009
DOI: 10.1103/physrevlett.103.230602
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Shear-Induced Cross-Correlations of Brownian Motion

Abstract: Shear-induced cross-correlations of particle fluctuations perpendicular and along streamlines are investigated experimentally and theoretically. Direct measurements of the Brownian motion of micron-sized beads, held by optical tweezers in a shear-flow cell, show a strong time asymmetry in the cross-correlation, which is caused by the non-normal amplification of fluctuations. Complementary measurements on the single particle probability distribution substantiate this behavior and both results are consistent wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…However, in reality, fluctuations always exist as manifested in the hydrodynamic instability (29) or the shear-induced Brownian motion (30), so that solutions of Eqs. 1 and 2 become very complicated because of mixing between various fluctuating stress and strain rate components.…”
Section: Significancementioning
confidence: 99%
“…However, in reality, fluctuations always exist as manifested in the hydrodynamic instability (29) or the shear-induced Brownian motion (30), so that solutions of Eqs. 1 and 2 become very complicated because of mixing between various fluctuating stress and strain rate components.…”
Section: Significancementioning
confidence: 99%
“…Brownian motion in nonequilibrium systems is of particular interest because it is directly related to the transport of molecules and cells in biological systems. Important examples include Brownian motors [38,39], active Brownian motion of self-propelled particles [40][41][42][43][44][45][46], hot Brownian motion [47], and Brownian motion in shear flows [48]. Recent theoretical studies also found that the inertias of particles and surrounding fluids can significantly affect the Brownian motion in nonequilibrium systems [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Other theoretical and experimental studies have also been conducted on fluctuations in NESS under shear flow by using systems other than immiscible blends [15][16][17][18][19][20][21][22][23][24] . For example, Sakaue et al [16] performed a theoretical investigation of a model system consisting of two beads connected by a harmonic spring under shear flow, showing that nonconservative forces caused by the shear flow violate the fluctuation dissipation theory (FDT) and deriving an alternative relation valid for NESS's.…”
Section: Introductionmentioning
confidence: 99%